Analisis Biaya Pemeliharaan Bangunan Gedung Dengan Konsep Green building Dan Bangunan Gedung Dengan Konsep Non Green building - Rika Apriani; Ida Ayu Ari Angreni (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
The concept of green building must also consider the cost of building maintenance in the post-construction stage so as not to reduce the large company costs each year. Green building is defined as a high-performance building that is made environmentally friendly, economically beneficial and healthy for life and workplace. This study intends to analyze the cost of building maintenance using the concept of green building non-green building. The data used in this study is the data on the maintenance costs of green buildings and non-green buildings. This data was taken by surveying the building management directly. Based on the analysis, the difference in the cost of maintaining green buildings and non-green buildings is Rp 10,283.22/m2/year. Based on the calculation, the maintenance costs of green building and non-green building still conform the standards of the Minister of Public Works Regulation and the standard of the Minister of Finance Regulation.